FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIABETES MELLITUS PADA PASIEN DI RSUD HAJI MAKASSAR - Jusman Usman; Dahlan Rahman; Rosdiana Rosdiana; Nurfayanti Sulaiman (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Diabetes mellitus (DM) is a chronic disease characterized by hyperglycemia and glucose intolerance that occurs because the pancreas gland cannot produce insulin adequately or because the body cannot use insulin that is produced effectively or both. This study aimed to determine factors related to the incidence of diabetes mellitus to patients inRSUD Haji Makassar. This type of research was observational with a cross sectional study approach. This research had a sample of 110 patients, sampling using simple random sampling method and data analysis was univariate and bivariate using chi-square test. The results of the study based on bivariate analysis stated that gender had a relationship with diabetes mellitus with a value of p = 0.002, there was a relationship between diet and diabetes mellitus with a value of p = 0,000, there was a relationship between sports habits with diabetes mellitus with a value of p = 0,000. While there was no relationship between family history with diabetes mellitus with a value of p = 0.938. The conclusion of this study is that there is a relationship between sex, diet and exercise habits related to diabetes mellitus, while family history is not related to diabetes mellitus. Researchers suggest for patients who are prone to diabetes mellitus to increase the intensity of physical activity and a balanced diet